Influence of Membrane Salt Rejection Properties on Cake-Enhanced Concentration Polarization Effects During Colloidal Fouling of Nanofiltration Membranes - Oranso Themba Mahlangu; Bhekie Brilliance Mamba (Membranes)
The build-up of a fouling layer on the membrane surface is believed to deteriorate flux and salt rejection by hindering back-diffusion of rejected salts, a phenomenon called cake-enhanced concentration polarization (CECP). Nevertheless, CECP effects have not been linked to the salt rejection properties of the membrane. Furthermore, the decline in salt rejection during fouling has not been related to the decreasing flux, to elucidate the effects of flux on solution rejection as described by the solution-diffusion (SD) model. Therefore, this work examined whether CECP is substantial in membranes with poor salt-rejection properties. Fouling was performed using sodium alginate, Al2O3, latex, and SiO2. The effects of fouling on salt rejection were studied using two nanofiltration (NF) membranes, namely NF270 membrane (46% NaCl rejection) and NF90 membrane (>97% NaCl rejection). The measured flux and salt rejection profiles were compared to those predicted by the CECP and SD models. Overall, the flux declined more (30–60%) for the NF90 membrane (contact angle: 50 ± 3°) compared to the NF270 membrane (10–55%, contact angle: 39 ± 2°) under similar hydrodynamic conditions. Moreover, fouling had more effects on NaCl rejection for the NF90 membrane (2–45% decline) compared to the NF270 membrane (10–30% decline). The decrease in NaCl rejection for the NF90 membrane was ascribed to CECP effects and declining flux. Contrary, CECP effects were less important for the NF270 membrane, and rejection declined due to reduction in flux as predicted by the SD model, indicating that CECP may not be predominant in membranes that poorly reject salts.